2003
DOI: 10.1097/01.sla.0000080823.38569.b0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Rectal Cancer Patients

Abstract: Anterior resection and nonstoma patients, despite suffering micturition and defecation problems, had better quality of life scores than abdominoperineal extirpation and stoma patients. Comparisons between abdominoperineal extirpation and anterior resection patients should consider the effect of temporary stomas. Improvements in quality of life scores over time may be explained by reversal of temporary stomas or physiologic adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
182
7
22

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(247 citation statements)
references
References 32 publications
29
182
7
22
Order By: Relevance
“…However, the majority of the respondents were 55-59 years old (36.3%), which is a relatively younger population age group. This is in agreement with studies from Western countries, such as that by Braun et al (2011) from the USA and by Engel et al (2003) from Germany; however, Tsunoda et al (2005) from Japan showed that the majority (43.0%) of their respondents were older than 70 years due to the ageing effect of the population.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, the majority of the respondents were 55-59 years old (36.3%), which is a relatively younger population age group. This is in agreement with studies from Western countries, such as that by Braun et al (2011) from the USA and by Engel et al (2003) from Germany; however, Tsunoda et al (2005) from Japan showed that the majority (43.0%) of their respondents were older than 70 years due to the ageing effect of the population.…”
Section: Discussionsupporting
confidence: 79%
“…The mean functional score in the present study ranged between 87.33 (IQR 16.71) and 95.21 (IQR 11.58). This is slightly higher than studies by Engel et al (2003) and Braun et al (2011). However, respondents' symptom scores in the present study are similar with other studies.…”
Section: Functional and Symptom Scoressupporting
confidence: 60%
See 2 more Smart Citations
“…Although in our study there was no statistically significant difference in body image between stoma and non-stoma users, previous studies showed statistically significant difference between them. A study from Germany showed that this difference persisted at end of years one, two and three post-diagnosis (Engel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%